Master: A radiometer for MM and sub-MM observations from the Antarctic Plateau - BOELLA, GIULIANO FILIPPO; GERVASI, MASSIMO; PASSERINI, ANDREA; SIRONI, GIORGIO; TARTARI, ANDREA; ZANNONI, MARIO; Natale, V. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2005)
A radiometer based on SIS mixers for astrophysical observations is being assembled. The system, cooled to cryogenic temperature by a pulse tube refrigerator, is intended for operation on the Antartic Plateau during the local winter, using the mm dishes available there in the futuro. The system prototype will be tested at the focus of the 2.6 m MITO telescope at the Testa Grigia Observatory on the italian Alps, We discuss the system characteristics and the observational programs.